Activity and dietary budgets of Tufted grey langurs (Semnopithecus priam priam). Issue 5 (3rd September 2021) - Vanaraj, Ganapathy; Pragasan, Lingassamy A.
Abstract : We collected the data of the activity budget and diet for a group of Tufted grey langurs Semnopithecus priam priam (TGL) in Pothigaiadi rural village from 2019 to 2020. This population is unstudied, and is near the eastern boundary of the species range adjacent to the Kalakad-Mundanthuarai Tiger Reserve (KMTR). We calculated the seasonal activity budget and diet composition by scan sampling from 96 full-day observations (dry season: 32, southwest monsoon: 32, and northeast monsoon: 32 days). During scan sampling, we recorded behavioural activities, and the food items and species consumed. TGL consumed 95 species of food plant, including trees and shrubs of 29 families. The food species varied seasonally. The annual activity budget of TGL is 31.88% social interaction, 23.57% resting, 23.27% feeding, 13.84% locomotion, 5.65% other activities, and 1.80% conflict. The overall diet of TGL consisted of 62.90% leaves, 7.81% mature fruits, 6.18% flowers, 5.85% tender leaves, 4.89% young fruits, 4.04% bark, 3.89% mud, 3.59% insects, and 0.85% water. The seasonal activity budget and diet composition of the TGL is discussed.